2021
DOI: 10.1111/rego.12385
|View full text |Cite
|
Sign up to set email alerts
|

Regulating for integration by behavioral design: An evidence‐based approach for culturally responsive regulation

Abstract: Democratic societies around the world face the challenge of strengthening social integration against a multitude of cultural and ethnic differences. Yet common regulations for integration – from cultural assimilation policies to general education programs – encounter objection, noncompliance, and even backlash among the very groups that the regulator strives to integrate into society. The article analyzes this challenge from a behavioral perspective, drawing on rich qualitative and experimental evidence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Predictably enough, BPP and RR also have mutual blind spots. For example, they do not pay sufficient attention to the role of culture and identity in shaping the relationship between individuals and governments, although several studies have showed that these factors may influence compliance substantially (e.g., Wenzel 2007; Gobena & Van Dijke 2017; Barak‐Corren 2021). In addition, both theories assume competent and benevolent regulators.…”
Section: Squaring Regulation and Free Markets: Two Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…Predictably enough, BPP and RR also have mutual blind spots. For example, they do not pay sufficient attention to the role of culture and identity in shaping the relationship between individuals and governments, although several studies have showed that these factors may influence compliance substantially (e.g., Wenzel 2007; Gobena & Van Dijke 2017; Barak‐Corren 2021). In addition, both theories assume competent and benevolent regulators.…”
Section: Squaring Regulation and Free Markets: Two Approachesmentioning
confidence: 99%
“…Moreover, expanding the assumptions regarding the regulatees and how they behave can inspire researchers to address types of regulatees that have rarely been included in BPP and RR studies, such as cultural and religious groups (Coleman & Freeman 1997; Barak‐Corren 2021; but see the adaptation of the enforcement pyramid to East Timor described in Job et al . 2007).…”
Section: Intersecting Rr and Bpp: Growing From Differencesmentioning
confidence: 99%
See 3 more Smart Citations